Complement inhibitory stent coating reduces inflammation and neointima formation in New Zealand white rabbits - Trück, J; Wendel, H; Janzen, J; Brehme, U; Tepe, G (2008)
Purpose: The purpose of this study was to investigate the role of inflammation during stent placement and the value of complement inhibition by stent coating with C1/C3 esterase inhibitor. Inflammation has been described as a major component of restenosis occurring after stent implantation. Methods: Animals were randomly assigned to one of 5 treatment groups and sacrificed after 4 days, and 6 weeks respectively. After 4 days uncoated bare metal control stents (C) (n=8) were compared with polyvinylpyrrolidone coated stents (P) (n=7), and after 6 weeks C stents (n=7) were compared with P stents (n=7) and P C1/C3 esterase inhibitor coated stents (PI) (n=7). AU morphometric measurements were performed on Elastica-van-Gieson stained segments, and the inflammation index (adapted from Kornowski et al.) was assessed using hematoxylin-eosin staining. Results: No acute or subacute thrombosis was observed. After 6 weeks neointima formation was 1.8±0.6 mm2 (bare stent) and 2.6±1.3 mm2 (P) in the control groups. In the treatment group (PI) neointima reduction was detectable (1.5±0.6 mm2). Inflammation was increased by P coating. In the PI stents the inflammation was significantly reduced compared to the P stents. Inflammation was noted 4 days after stent implantation with granulocytes whereas mononuclear infiltrates (lymphocytes, plasma cells) were predominant after 6 weeks. Conclusions: Inflammation is a key component of restenosis following stent administration. Inflammation can be reduced by C1/C3 esterase inhibitor coated stents. Because the hydrogel coating itself induced inflammation, this coating seems not to be the ideal for intravascular use. © Verlag PERFUSION GmbH.